Dinâmica da magnetização e ruído Barkhausen em multicamadas ferromagnéticas - Machado, Núbia Ribeiro (2020)
In this work, we focus on the study of Barkhausen noise in ferromagnetic multilayer films using the traditional inductive method and the statistical properties of Barkhausen jumps. Motivated by the results obtained in polycrystalline and amorphous films with different thicknesses, through the method, we investigate the dynamics of magnetization through critical exponents of the distributions of area, duration, average area and power spectrum, obtained experimentally, to understand the effects the dimensionality of the system and the range of interactions on exponents, due to the movement of domain walls. Specifically, we obtained Barkhausen noise time series for multilayer films with Co40Fe40B20(10 nm)/Ag(2 nm), Co40Fe40B20(10 nm)/Ta(2 nm) e Ni81Fe19(10 nm)/Ag(2 nm) e Ni81Fe19(10 nm)/Ta(2 nm), with different number of stacked ferromagnetic bilayers, where Tantalum (Ta) and Silver (Ag) are used as a non-magnetic spacer. In this case, it was observed that the exponents obtained experimentally, when compared to theoretical models, present three-dimensional magnetic behavior with long-range dipolar interaction, regardless of the number of stacked bilayers, the spacer and the frequency of the applied external magnetic field, suggesting a single universality class for the set of exponents. However, the data reveal a dynamics of modified or artificially structured three-dimensional DWs due to the act of ferromagnetic layers with two-dimensional magnetic behavior. In particular, dependence on exponents τ and α on the field frequency for polycrystalline multilayers, a fingerprint of field theory-medium that describes threedimensional polycrystalline magnetic materials. Finally, considerations are made about a possible coupling between the overlapping layers, as an indicator of the stability of the exponents.